Penguatan Identitas Bangsa melalui Pendidikan Multikultural Tinjauan Lanjutan dari Galatia 5:22-23: Menurut Prespektif Sosiologi - Lubis, Menti Riani (JURNAL KADESI, 2024)
Indonesia, a country rich in social, ethnic, linguistic and religious diversity, has upheld solidarity in diversity since independence in 1945. The motto "Bhineka Tunggal Ika" serves as a reminder of the importance of respecting cultural, religious, ethnic and racial diversity. Multicultural education, according to Agustian, is an approach that highlights social pluralism and differences in various aspects. It should be taught from an early age in order to create an inclusive and supportive learning environment. Multicultural education also aims to uphold fundamental rights, norms of justice and intercultural understanding, which in turn strengthens social cohesion and national identity. The research method used in this article is a descriptive qualitative literature review. This article examines the strengthening of national identity through multicultural education using a sociological approach and applying principles from Galatians 5:22-23 such as love, joy, peace, patience, kindness, goodness, faithfulness, gentleness and self-control. The results show that multicultural education promotes values such as equality, inclusion and justice, which are important for building a peaceful and inclusive society. The implementation of Galatians 5:22-23 values in multicultural education can be done through curriculum development, teacher training and activities that encourage interaction between students from different cultural backgrounds. In conclusion, multicultural education plays an important role in strengthening national identity by instilling values of togetherness and respect for differences, as well as strengthening social cohesion and national identity.